Literature Review on Green Cost Premium of Sustainable Building Construction - Russ, Nazirah Mat; Hanid, Mahanim; Kho, Mei Ye (Faculty of Engineering, Universitas Indonesia, 2018)
Despite evidence that sustainable construction practice has numerous environmental, economy and societal benefits, many construction practitioners have failed to support sustainable construction practice due to perceive higher initial cost known as 'green cost premium' when compared to traditional construction practice. Hence, the factors of green cost premium that are commonly cited as a crucial barrier toward sustainable construction practice must be investigated. Based on the analysis of the existing literature (e.g.: conference paper, journal article), there are 27 factors, that classified into seven elements, that contribute to the cost differential. However, few studies have been conducted on green cost premium in developing countries. Therefore, this study attempts to fill this gap and is expected to contribute to the discussion on green cost premium to improve sustainable construction implementation.